2016
DOI: 10.1111/xen.12276
|View full text |Cite
|
Sign up to set email alerts
|

Development of retrocorneal membrane following pig‐to‐monkey penetrating keratoplasty

Abstract: Introduction Recent reports of long-term survival after wild-type (WT) pig-to-monkey corneal xenotransplantation are encouraging. We experienced the rapid development of retrocorneal membranes, a rare complication after corneal allotransplantation (though seen in infants and young children). The original specific aim of the study was to determine the factors associated with successful (young) pig corneal transplantation in monkeys. However, when it was obvious that retrocorneal membranes rapidly developed, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…By eliminating αGal‐related reaction, GTKO pig corneal grafts should survive longer than wild‐type (WT) grafts . However, previous studies have reported otherwise in non‐human primates (NHPs) . Although the rejection mechanism in GTKO pig corneal xenotransplantation remains controversial, there are two possibilities for graft failure: (a) antibody (Ab)‐mediated rejection may still occur although GTKO lacks αGal or (b) disparity of the corneal thickness may affect survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By eliminating αGal‐related reaction, GTKO pig corneal grafts should survive longer than wild‐type (WT) grafts . However, previous studies have reported otherwise in non‐human primates (NHPs) . Although the rejection mechanism in GTKO pig corneal xenotransplantation remains controversial, there are two possibilities for graft failure: (a) antibody (Ab)‐mediated rejection may still occur although GTKO lacks αGal or (b) disparity of the corneal thickness may affect survival.…”
Section: Introductionmentioning
confidence: 99%
“…Donor and recipient corneal thickness must be matched for optimal wound approximation. Genetically engineered non‐miniature pig cornea is thicker than miniature pig cornea of the same age; therefore, younger donors (≤3‐month‐old) were used in previous studies . However, younger donor corneas are too flaccid to handle properly, resulting in severe inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…However, these potent immunosuppressive regimes cannot be applied clinically since they may cause severe side effects in case of long‐term use. Furthermore, the thickness disparity between porcine cornea and host bed may lead to several postsurgical complications which may cause grafting failures, such as shallow anterior chamber, secondary glaucoma, anterior synechia, and retro‐corneal membrane …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the thickness disparity between porcine cornea and host bed may lead to several postsurgical complications which may cause grafting failures, such as shallow anterior chamber, secondary glaucoma, anterior synechia, and retro-corneal membrane. 11,12 Endothelial keratoplasty (EK), only replacing the recipient endothelial layer with healthy endothelium, has become the predominant treatment for endothelial impairments in developed countries. In the US, the number of EK is almost equal to that of penetrating keratoplasty (PKP) nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al recently published their initial results of GTKO.hCD46 pig full-thickness corneal xenografts in NHPs, which were comparable to the survival of wild-type pig corneas [54]. Lee et al provided evidence that the limiting factor of survival of pig corneas was the development of a retrocorneal membrane [55]. The Seoul group recently reported prolonged survival (>389 days) of porcine deep-lamellar corneal xenografts in NHPs under immunosuppressive therapy with anti-CD40mAb (Figure 2) [56].…”
Section: Introductionmentioning
confidence: 99%